2016
DOI: 10.1111/evj.12649
|View full text |Cite
|
Sign up to set email alerts
|

The development of locomotor kinetics in the foal and the effect of osteochondrosis

Abstract: SummaryReason for performing studyFoals stand and walk immediately after birth, but insight into the subsequent longitudinal development of their gait kinetics in the early juvenile phase and the possible influence of osteochondrosis thereon is lacking.ObjectivesTo quantify gait kinetics in foals during the first half year of life, taking into account their osteochondrosis status.Study designProspective, cohort study performed at a single stud farm.MethodsPressure plate measurements at walk and trot from 11 Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
1
15
1
Order By: Relevance
“…Already during the first weeks of life, a significant reduction in variability was observed. This is in line with the rapid initial improvement of static balance [3] and the significant reduction in variability of the stance duration [2] observed in young foals and is likely due to better control thanks to the maturation of the neuromuscular system. In a stabilographic study cranio-caudal sway amplitudes that were larger than those in medial-lateral direction shortly after birth [3].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Already during the first weeks of life, a significant reduction in variability was observed. This is in line with the rapid initial improvement of static balance [3] and the significant reduction in variability of the stance duration [2] observed in young foals and is likely due to better control thanks to the maturation of the neuromuscular system. In a stabilographic study cranio-caudal sway amplitudes that were larger than those in medial-lateral direction shortly after birth [3].…”
Section: Discussionsupporting
confidence: 82%
“…Osteochondrosis was not a significant factor in our models, while there was a small, yet significant effect of OC on kinetic parameters in our previous study . Hence, the minor changes observed in kinetic parameters due to subclinical lameness (resulting in a reduction of nPVF in the affected limb) are not reflected in the hoof‐balance ASI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speed at walk and trot increased, whereas peak vertical force, normalised to body weight, stayed constant. Foals with subclinical osteochondrosis lesions showed a temporary reduction in peak vertical force [11]. These studies suggest that pressure plates may represent useful tools for the regular monitoring of horses and may have the potential to detect subclinical lameness.…”
Section: Early Detection Of Lamenessmentioning
confidence: 78%
“…Another study by the same authors aimed at quantifying gait kinetics in foals during the first half year of life, taking into account their osteochondrosis status. This showed that during growth, velocity at walk and trot gradually increases, while maintaining normalised peak vertical force; and that a temporary reduction in normalised peak vertical force was detected in osteochondrosis positive foals in the absence of lameness . These findings in young horses should be taken into account when foals are presented with gait disturbances.…”
mentioning
confidence: 89%